[PP.21.30] ELEVATED PREVALENCE OF EARLY VASCULAR AGING IN YOUNG ADULTS IN LATIN AMERICA: A CALL FOR ACTION? OPTIMO STUDY RESULTS. (September 2017) - Botto, F.; Obregon, S.; Di Leva, A.; Koretzky, M.; Forcada, P.; Brandani, L.; Scuteri, A.; Nilsson, P.M.; Kotliar, C.
Abstract : Objective: Early Vascular Aging (EVA) represents an arterial wall damage at an earlier age than expected by natural aging. It is dominated by an increased arterial stiffness and predicts a high cardiovascular risk. Our main objective was to analyze the prevalence of EVA in a population of Latin America with emphasis in young adults. Design and method: recruited 1416 subjects from 13 countries in Latin America who provided information about lifestyle, cardiovascular risk factors and anthropometrics. We performed a measurement of pulse wave velocity (PWV) as a marker of arterial stiffness and blood pressure (BP), by use of Mobil-O-Graph. To determine the prevalence of EVA we estimated PWV adjusted by age and systolic BP in a multiple linear regression model and compared expected versus observed PWV. Then, we analyzed standardized residuals (z-scores) of adjusted PWV applying Observed PWV - Expected PWV / SD of Expected PWV. We defined EVA when z-score was > = 1.96. Finally, we performed multivariable logistic regression analysis to determine variables associated to EVA in all the subjects and in young adults (<41 years-old). Results: Mean age was 49.9 ± 15.5 years-old, male gender was 50.3%. Mean PWV was 7.52 m/s (+−1.97) and mean systolic BP was 125.29 mmHg (+−16.78). Z-score analyses determined that observed PWV values were predicted by age and systolic BP in 1272 subjects (89.8%). The remaining 81 (5.7%) cases represent the observed prevalence of EVA and 63 (4.4%) the prevalence of low PWV. Prevalence of EVA restricted to adults <41 years-old was 9.8% (37/376) and <31 years-old was 18.7% (30/160). Multiple logistic regression analysis showed that dyslipidemia, hypertension and regular alcohol intake (p < 0.05) were independently associated to EVA in young adults. Body mass index showed a borderline association (p = 0.06). Conclusions: After adjusting PWV for age and systolic BP, the observed prevalence of EVA in young adults in Latin America was very high, around 1 out of 10 and 1 out of 5 in those who were 40 and 30 years old or less, respectively. These results call for efforts to investigate, diagnose and treat cardiovascular risk factors from youth.